2020
DOI: 10.1016/j.enbuild.2020.110298
|View full text |Cite
|
Sign up to set email alerts
|

Does telecommuting save energy? A critical review of quantitative studies and their research methods

Abstract: Highlights Telework impacts transportation, building, and Internet-related energy and emissions. Telework’s environmental impact is highly dependent on contextual details. The majority of studies indicate telework decreases energy use, with some exceptions. Rebound effects tend to significantly offset and even exceed energy savings. Existing research methods tend to be simple, leaving room for significant improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 95 publications
(183 reference statements)
0
94
0
Order By: Relevance
“…In general, when there are fewer communication cues presented, those particular cues have a larger impact than when there are many cues available (Walther, 1996, or see Walther et al, 2015, for a review). But it is important to note that most of the work on the number of cues in computer-mediated communication has examined linguistic cues, not the video (though see Nowak et al, 2005, for a notable exception). Future work should examine how the number of cues impacts person perception during the realtime video.…”
Section: Cognitive Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, when there are fewer communication cues presented, those particular cues have a larger impact than when there are many cues available (Walther, 1996, or see Walther et al, 2015, for a review). But it is important to note that most of the work on the number of cues in computer-mediated communication has examined linguistic cues, not the video (though see Nowak et al, 2005, for a notable exception). Future work should examine how the number of cues impacts person perception during the realtime video.…”
Section: Cognitive Loadmentioning
confidence: 99%
“…Moreover, if the practice of taking meetings virtually endures postpandemic, fossil fuel consumption should decrease due to a reduction in physical commuting. For example, one study demonstrated that videoconferencing uses less than 10% of the energy required for an in-person meeting (Ong et al, 2014), and a recent review demonstrates that a majority of studies have demonstrated that telecommuting saves energy (O'Brien & Yazdani Aliabadi, 2020).…”
mentioning
confidence: 99%
“…Hook et al [86] stated that despite the generally positive verdict, there are uncertainties and ambiguities about the actual benefits in energy saving. O'Brien and Aliabadi (2020) [87] suggested that the rebound effect of telework tends to offset and even exceed energy savings significantly. The factors which could affect the energy consumption of the comparative options could be summarised as: Commuting distance (e.g.…”
Section: Energy-related Lessons and Emerging Opportunitiesmentioning
confidence: 99%
“…While the studies' results vary widely because each study had different contexts (e.g., methods, assumptions, proportions of teleworking, scope, etc. ), most studies indicate moderate energy savings, with more empirically rigorous methodologies typically finding more modest savings (O'Brien and Yazdani Aliabadi 2020;Hook et al 2020;Giandomenico, Papineau, and Rivers 2020).…”
Section: Teleworking and Energymentioning
confidence: 99%